Monitoring and Evaluation of Education in Nigeria: Challenges and Ways Forwards - Ogunode Niyi Jacob; Adah Samuel; Wama Pajo; Audu Elizabeth I (International Journal on Orange Technologies, 2020)
- The article discusses the challenges preventing effective monitoring and evaluation of education in Nigeria. Secondary data was used to support the points raised in the article. The secondary data were sourced from print material and online publication by recognized institutions and individual author. There are many challenges militating against effective monitoring and evaluation of educational programme in Nigeria. Some of the challenges include; inadequate funding of monitoring and evaluation programmme, inadequate professional monitoring and evaluating officers, poor capacity development of monitoring and evaluating officers, corruptions, insecurity, inadequate monitoring and evaluation tools, political instability and lack of political support. To solve this challenges, this article recommends the following: the government should provide: adequate funding for monitoring and evaluation programmme, employment of more professional evaluator and monitors, constant capacity development programme for monitoring and evaluating officers, fight all institution corruption, provide security for Monitoring and Evaluating officers, provide adequate monitoring and evaluation tools, ensure political stability and the political officeholders should support the activities of monitoring and evaluation in the country.